2004
DOI: 10.1101/gr.2231904
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Genomes as New Gene Homes: The Genealogy of ORFans in E. coli

Abstract: Differences in gene repertoire among bacterial genomes are usually ascribed to gene loss or to lateral gene transfer from unrelated cellular organisms. However, most bacteria contain large numbers of ORFans, that is, annotated genes that are restricted to a particular genome and that possess no known homologs. The uniqueness of ORFans within a genome has precluded the use of a comparative approach to examine their function and evolution. However, by identifying sequences unique to monophyletic groups at increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
259
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(287 citation statements)
references
References 44 publications
25
259
1
2
Order By: Relevance
“…The majority with significant BLAST (61) hits match genomes of closely related Sulfolobales species or their mobile elements (Table S3), suggesting that horizontal gene transfer from divergent species is a rare event. As in other analyses of microbial species (40,45,59,60,63), many of the gained genes in S. islandicus have no significant BLAST match to the public databases (Table S3).…”
Section: Biogeography Of the Variable Genomementioning
confidence: 99%
“…The majority with significant BLAST (61) hits match genomes of closely related Sulfolobales species or their mobile elements (Table S3), suggesting that horizontal gene transfer from divergent species is a rare event. As in other analyses of microbial species (40,45,59,60,63), many of the gained genes in S. islandicus have no significant BLAST match to the public databases (Table S3).…”
Section: Biogeography Of the Variable Genomementioning
confidence: 99%
“…Support for this hypothesis has been given by the studies of Domazet-Loso and Tautz (2003) and Daubin and Ochman (2004), in Drosophila and bacteria, respectively. In the present study, this hypothesis has been further tested with respect to the Ascomycotan fungi.…”
Section: Discussionmentioning
confidence: 90%
“…A proposed explanation of this problem has been that some genes evolve so rapidly that their homologues cannot be discovered over larger evolutionary distances (Schmid and Aquadro 2001). Although this has been supported by recent findings in Drosophila and bacteria that orphan genes evolve, on average, more than three times faster than nonorphan genes (Daubin and Ochman 2004;Domazet-Loso and Tautz 2003), the influence of other factors on the evolutionary rate of genes should be taken into account. These factors include the expression level of genes (Hastings 1996;Pal et al 2001), a gene's dispensability (the organism's fitness after deletion of the gene) (Hirsh and Fraser 2001;Krylov et al 2003), gene essentiality (Wilson et al 1977), gene duplication (Jordan et al 2002b;Yang et al 2003), and the number of protein-protein interactions involving the gene's product (Fraser et al 2003;Wagner 2001).…”
Section: Introductionmentioning
confidence: 93%
“…As described above, DNA of lateral origin has passed filters that can skew its composition. In most g-proteobacteria, ORFans (genes without significant matches in current databases) are AþT-rich, suggesting a phage ancestry Daubin & Ochman 2004). Successive LGT events can superimpose DNA onto previously incorporated regions, resulting in a genomic pastiche that may defy analysis; Chan et al (2009) found that 5.5 per cent of 1462 orthologue families exhibit complex recombination patterns consistent with successive layering of LGT.…”
Section: Quantificationmentioning
confidence: 99%
“…The relative contribution of each LGT process is not well understood, but in many cases the processes leave tell-tale clues (Zaneveld et al 2008). ORFans in bacteria are often enriched in A þ T compared with the rest of the genome, suggesting residence in bacteriophage (Daubin & Ochman 2004). Genes on plasmids often show divergent nucleotide composition (Nakamura et al 2004) and phylogenetic relationships (Gerdes et al 2000) indicative of xenologous origin.…”
Section: (B)mentioning
confidence: 99%